Roles of Toll-Like Receptor 3 in Human Tumors - Zheng, Xin; Li, Song; Yang, Hui (Frontiers in Immunology, 2021)
Toll-like receptor 3 (TLR3) is an important member of the TLR family, which is an important group of pathogen-associated molecular patterns. TLR3 can recognize double-stranded RNA and induce activation of NF-κB and the production of type I interferons. In addition to its immune-associated role, TLR3 has also been detected in some tumors. However TLR3 can play protumor or antitumor roles in different tumors or cell lines. Here, we review the basic signaling associated with TLR3 and the pro- or antitumor roles of TLR3 in different types of tumors and discuss the possible reasons for the opposing roles of TLR3 in tumors.